Assessment of Oral Cancer: A Study in Nepal Cancer Hospital and Research Center, Harisiddhi, Lalitpur, Nepal. - Thapa, Kapil; Jaiswal, Puja (Journal of Institute of Science and Technology, 2022)
Oral cancer is becoming very common and increasing day by day in Nepal. It ranks 6th in the world and 5th in Nepal among all types of cancer as of 2018.  This is a hospital-based retrospective study. Required details of 128 patients who underwent surgery from 1st April 2018 to 30th October 2019 in Nepal Cancer Hospital and Research Center, Lalitpur. Data were collected age-wise, sex-wise, site-wise, and stage-wise prevalence was figured out. The data were analyzed using MS excel 2007. It was found that males were more commonly affected than females with the mean age for males at diagnosis being 53.3 years and females being 55.62 years. The tongue was the most affected site followed by GBS then buccal mucosa and RMT. Most people knew about cancer growing on them only at advanced stages.